Increasing Knowledge of Future Brides in Preparing for Marriage through E-Learning Based Health Education (E-CATIN): Peningkatan Pengetahuan Calon Pengantin Dalam Mempersiapkan Pernikahan melalui Edukasi Kesehatan Berbasis E-Learning (E-CATIN) - Nurul Hidayah; Anja Hesnia Kholis; Pepin Nahariani; Ahmad Nur Khoiri; Alex Srihono; Lucas Magalhaes (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Increased Knowledge of future bride on Preparing Marriage and increasing the scope of guidance future bride in the Office of Religious Affairs (KUA) with the application of E-CATIN. Methods: Quasy Experimental Research Design with pre-post-test two group (intervention group and control group). Results: Paired T-Test Sig values of 0.000< 0.05 in the E-CATIN intervention group, 0.011< 0.05 in the control group. Then the results of the Independent T Test are 0.000 < 0.05, meaning that there is a significant difference Conclusion: The influence of the E-CATIN Application on the level of knowledge of prospective brides in wedding preparation includes physical health, mental health, economic welfare, spiritual and cultural adaptation in KUA Diwek District, Jombang Regency. The development of information systems and if applied positively also has a positive effect on the reach or achievement of future bride guidance in pre and post wedding preparation.